Privacy protection for patients with substance use problems - Hu LL; Sparenborg S; Tai B (Dove Medical Press, 2011)
Lianne Lian Hu1, Steven Sparenborg2, Betty Tai21Department of Preventive Medicine and Biometrics, Uniformed Services University of the Health Sciences, 2Center for the Clinical Trials Network, National Institute on Drug Abuse, National Institutes of Health, Bethesda, MDAbstract: Many Americans with substance use problems will have opportunities to receive coordinated health care through the integration of primary care and specialty care for substance use disorders under the Patient Protection and Affordable Care Act of 2010. Sharing of patient health records among care providers is essential to realize the benefits of electronic health records. Health information exchange through meaningful use of electronic health records can improve health care safety, quality, and efficiency. Implementation of electronic health records and health information exchange presents great opportunities for health care integration, but also makes patient privacy potentially vulnerable. Privacy issues are paramount for patients with substance use problems. This paper discusses major differences between two federal privacy laws associated with health care for substance use disorders, identifies health care problems created by privacy policies, and describes potential solutions to these problems through technology innovation and policy improvement.Keywords: substance abuse, patient privacy, electronic health records, health information exchange